Social isolation, loneliness, socioeconomic status, and health-risk behaviour in deprived neighbourhoods in Denmark: A cross-sectional study - Maria Holst Algren; Ola Ekholm; Line Nielsen; Annette Kjær Ersbøll; Carsten Kronborg Bak; Pernille Tanggaard Andersen (Elsevier, 2020)
The importance of social isolation and loneliness on our health is widely recognised in previous research. This study compares loneliness in deprived neighbourhood with that in the general population. It further examines whether social isolation and loneliness are associated with health-risk behaviours (including low intake of fruit or vegetables, daily smoking, high-risk alcohol intake, and physical inactivity and their co-occurrence) in deprived neighbourhoods, and whether social isolation and loneliness modify the associations between socioeconomic status and health-risk behaviours. Cross-sectional data from 5113 residents of 12 deprived neighbourhoods in Denmark were analysed using multiple logistic regression. Data on 14,686 individuals from the nationally representative Danish Health and Morbidity Survey 2010 were used as a comparison group with regard to loneliness. Cohabitation status, frequency of meeting with family and friends, participation in voluntary work were used as an indicator to measure social isolation. A question on feeling often unwillingly alone was used as an indicator to measure loneliness. Compared with the general population, residents of deprived neighbourhoods had higher odds of loneliness. Both social isolation and loneliness were significantly associated with higher odds of health-risk behaviour. When social isolation and loneliness were combined with low socioeconomic status, strong associations with health-risk behaviours were found. Social isolation and loneliness did not significantly modify the associations between socioeconomic status and health-risk behaviour. The findings in this study have important implications for the future planning of health promotion intervention programmes aimed to reduce health-risk behaviour in deprived neighbourhoods.